The plant characters and corm production of taro as catch crop under the young rubber stands (Biodiversitas Journal of Biological Diversity, 2006)
The research was aimed at revealing the chlorophyll content, leaf area (the plant characters), and the corm production of taro as catch crop under the young rubber stand. This research was conducted by means of Nested Design with nine replication. The intercropping planting used independent variables i.e. N0 (open condition), N1 (under the two-year-old young rubber), and N2 (under the three-year-old young rubber). The dependent variables were the chlorophyll content, leaf area, and production of the taro corm. The parameters investigated were the leaves area, the chlorophyll a and b content, the weight of fresh corm, the weight of dry corm, and the corm production per plots. The research result showed that the leaves area, and the chlorophyll a and b content significantly increased, while the weight of fresh corm, and the weight of dry corm significantly decreased (P